Research on the Defense of Advanced Persistent Threats in Enterprise Network - Dongxin Liu; Guorong Liu; Shuai Wang; Jun Shen; Huamin Jin (Dianxin kexue)
Recently,advanced persistent threats have become a hot spot of information security industry as so many reports were taken about that some famous companies had been suffered from it. The features of APT and the reason why traditional security defense architecture was failed were discussed. After that, a solution was proposed to build a PDRR defense model. In the end, the impacts that APT brings in was discussed.